Metabolic consequences of immune checkpoint inhibitors: A new challenge in clinical practice. (July 2020) - Parthymos, Ioannis; Liamis, George; Dounousi, Evangelia; Pentheroudakis, George; Mauri, Davide; Zarkavelis, George; Florentin, Matilda
Highlights: Immune Checkpoint Inhibitors (ICPIs) are a new a class of anti-cancer drugs, that are used in various types of cancers. ICPIs may cause side effects of immune origin the so-called immune related adverse events (irAEs). IrAEs frequently present with various clinical manifestations. Therefore, clinicians should be familiar with them. Treatment of irAEs may be challenging and depends on the severity of symptoms. Abstract: Treatment of oncologic patients has progressed greatly the last few years with the development of immune checkpoint inhibitors (ICPIs). These drugs are associated with the immune system and, thus, may cause side effects of immune origin, the so called immune related adverse events (irAEs). Immune related AEs may actually affect all organs and systems and frequently resemble clinical entities commonly encountered in clinical practice. As ICPIs have improved both quality of life and life expectancy, clinicians of various specialties may need to deal with irAEs in their everyday practice. Therefore, they should be able to recognize them timely and treat them accordingly. Herein, we review the pathophysiology, clinical manifestations and treatment of irAEs.